2016
DOI: 10.1073/pnas.1609990113
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for norovirus neutralization by an HBGA blocking human IgA antibody

Abstract: Human noroviruses (HuNoVs) cause sporadic and epidemic gastroenteritis worldwide. They are classified into two major genogroups (GI and GII), with each genogroup further divided into multiple genotypes. Susceptibility to these viruses is influenced by genetically determined histo-blood group antigen (HBGA) expression. HBGAs function as cell attachment factors by binding to a surface-exposed region in the protruding (P) domain of the capsid protein. Sequence variations in this region that result in differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 64 publications
4
51
0
Order By: Relevance
“…Four α-GI mAbs isolated from chimpanzees challenged with norovirus blocked VLP binding to carbohydrates and inhibited hemagglutination, although their precise binding sites were not described [20]. Recently, a GI.1 specific mAb was discovered that sterically hindered the HBGA pocket [22]. In our study, we showed that Nano-14 overlapped with the GII.10 HBGA binding sites and inhibited HBGA binding by steric interference and competition for the pocket.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Four α-GI mAbs isolated from chimpanzees challenged with norovirus blocked VLP binding to carbohydrates and inhibited hemagglutination, although their precise binding sites were not described [20]. Recently, a GI.1 specific mAb was discovered that sterically hindered the HBGA pocket [22]. In our study, we showed that Nano-14 overlapped with the GII.10 HBGA binding sites and inhibited HBGA binding by steric interference and competition for the pocket.…”
Section: Discussionmentioning
confidence: 59%
“…For example, in the case of HIV, with the aid of an extra long CDR3 loop, the neutralizing Nanobody D7 effectively competed for the CD4 binding site on gp120 protein [42]. Previously described Nanobodies and mAbs with therapeutic potential against human norovirus were also proposed to interfere with the HBGA binding site [20,[22][23][24][25][26][27]. MAb termed NV8812 bound to a conformational epitope on the GI.1 P domain and blocked the binding of norovirus VLPs to human and animal cell lines [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…81 Likewise, V H Hs targeting the HBGA-binding pocket of norovirus VP1 neutralized a broad range of genotypes, 82 while larger conventional antibodies also made contact with antigenically variable residues surrounding the HBGA pocket and were thus strain-specific. 83 …”
Section: Single-domain Antibodies Directed Against Folded Proteinsmentioning
confidence: 99%
“…Recently the structure of one such human antibody in complex with the NV P-domain was determined and it revealed steric hindrance as the mechanism of HBGA blockade [23]. Other structural studies have shown that human milk oligosaccharides, 2′-fucosyllactose (2′FL) and 3′-fucosyllactose (3′FL) and molecules like citrate mimic HBGA binding, thus serving as decoy receptors and potential glycomimetics [24,25].…”
Section: Hbga Recognition By Human Novsmentioning
confidence: 99%